STUDY OF PROGO RIVER MORPHOLOGY AND SEDIMENTATION OF INTAKE KAMIJORO WEIR BANTUL REGENCY, SPECIAL DISTRICT OF YOGYAKARTA - Uzaer, Mukhammad
Irrigation Intake DI Pijenan (2370 hectares) at Kamijoro Weir Progo River, Bantul Regency is experiencing sedimentation problems and blockages due to garbage (stone and wood), so that the intake does not function optimally. BBWS Serayu Opak, Ministry of Public Works and Housing has made efforts by carrying out routine dredging and construction of a Trashrack aimed at controlling sedimentation and waste in front of the Intake. A comprehensive analysis using the morphological and hydraulic changes approach shows that the intake position has a tendency to change the river channel pattern (meander). Besides that, the sediment transport rate of the Progo River is very large because it originates at Mount Merapi, which is still actively releasing eruptions and cold lava, besides that the rate is triggered by erosion of critical river watershed lands (land erosion > 3mm/year). For this reason, an alternative solution is needed to overcome sedimentation hydraulically, namely using the KRIB building on the side of the channel around the intake. In this study, analysis was carried out using HEC-RAS 6.1 software, both sedimentation and flow velocity. The simulation results of HE-CRAS 6.1 TMA 2D software and HEC-RAS 6.1 Sediment 1D conditions before and after installing KRIB on the right side of the river, showed that after installing KRIB there was a reduction of 66.67% (bankfull condition) and 79.31% (100th flood condition). Based on the Hjulstorm chart, in the condition after KRIB was installed, it showed that it was in the Transport in Suspension area, where the sediment grains in front of the intake can be carried away by water velocity in Bankful conditions. The simulation shows that there is a change in the morphology of the bottom and riverbanks around the intake which has a tendency to reduce sedimentation due to the deflection of the current towards the intake position, so that the construction of KRIB can complete sedimentation at the intake in the long term.